Reflective boot camp: adapting LEGO® SERIOUS PLAY® in higher education. Issue 2 (4th March 2017) - Peabody, Mary Anne; Noyes, Susan
Abstract: This qualitative study investigates the experiences of using an adaptation of LEGO® SERIOUS PLAY® as a reflective practice pedagogy with occupational therapy graduate-level students and faculty. LEGO® SERIOUS PLAY® is an innovative facilitated methodology that uses brick-building and metaphoric storytelling as a form of communication and problem-solving. Participants engaged in a four-step kinesthetic experience as a means to achieve a serious objective. Results of the study indicated affirmative participant outcomes that included: accelerated group cohesion; an appreciation for inclusive learning where student voice was amplified; a language for emotional content and deeper meaning-making; and an experiential process using materials that appealed to various learning styles. A small number of participants experienced minor tension with the process provoking unanticipated reflective learning. The results of this study indicate that using the kinesthetic brick modeling methodology for reflective practice is a promising higher education pedagogical option.